Advanced AutoCAD 2017 : advanced tools and techniques for computer aided design (CAD) - Benton, Brian C. (O'Reilly, 2016)
"In this Advanced AutoCAD 2017 training course, expert author Brian Benton teaches you about advanced tools and techniques in the latest version of AutoCAD. This course is designed for users that are already familiar with AutoCAD. You will start by learning about drawing navigation, then jump into learning about advanced operations. From there, Brian will teach you about advanced tools in AutoCAD, as well as object visibility and annotation. This video tutorial also covers sheet sets, output, and when and how to use data. You will also learn about dynamic blocks, parametric constraints, action recorder, and customization. Finally, you will learn about file management, and Autodesk cloud services. Once you have completed this computer based training course, you will have gained a solid understanding of the advanced tools and concepts in AutoCAD. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.